Идентификация напряженно-деформированных состояний составного цилиндра по известным смещениям - Сергиенко, И.В.; Дейнека, В.С. (Проблемы управления и информатики, 2009)
Представлено явні вирази градієнтів функціоналів-нев’язок для ідентифікації градієнтними методами різноманітних параметрів задач пружного деформування складеного кругового циліндра. Explicit expressions of gradients of functionals-discrepances for identification by gradient methods of different parameters of the problems of compound circular cylinder elastic deformation are represented.